Juvenile Polyp with Osseous Metaplasia Presenting with Fecal Incontinence in Young Patient : Case Report of Unusual Presentation - Fatima Alrowaiei; Mohammed Awadh (Journal of the Bahrain Medical Society)
Osseous metaplasia is rare in colorectal lesions and exceedingly rare in colonic polyps. We present a case report of rectal juvenile polyp with stromal osseous metaplasia in a 21-year-old male who presented with fecal incontinence episodes throughout the day and night over the past 2 years. The patient underwent a colonoscopy and polypectomy, which showed a juvenile polyp with osseous metaplasia. The patient’s primary concern was to fully recover postoperatively. Juvenile polyp with osseous metaplasia may be added to the differential diagnosis of patients with fecal incontinence. This work aims to discuss pathogenesis and review the literature on this rare condition.